If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 2x + 5 Reorder the terms: 12 + 3x = 2x + 5 Reorder the terms: 12 + 3x = 5 + 2x Solving 12 + 3x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 3x + -2x = 5 + 2x + -2x Combine like terms: 3x + -2x = 1x 12 + 1x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 1x = 5 + 0 12 + 1x = 5 Add '-12' to each side of the equation. 12 + -12 + 1x = 5 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 5 + -12 1x = 5 + -12 Combine like terms: 5 + -12 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 6+16n=-7 | | 6+6c=7c | | 5x-5=2(2x+3)-1 | | 0.5x-8=0.10x-9 | | 7x-2=4x+8 | | 2+3.50g=5-3.25g | | 10r^2+17r-20=0 | | 2-(x+6)=4(-3-x)+5 | | F(y-6)=2y-5 | | 5(2.5*t)= | | 5y-5=-30 | | 6+16n=7 | | 50=100 | | 10b-2-2=7b-7.4 | | (x-3)(4-x)=15 | | 11(v+2)-3v=4(2v+3)-13 | | 5x(2.5xt)= | | 3(3x-7)=16 | | -x^2+12x-12=15 | | -2b-3=-11 | | 26=2u-10 | | 5v+17=52 | | -13n+8n=15 | | 180/n=120 | | L=x+200y | | 9-3z+4+6z-2= | | .04(2c-26)=-0.8(c-2) | | 42k^2+318k-540=0 | | y=.66666666666(-2)+3 | | 15v-14v=10 | | -6x-15=-7x+6 | | 1/2(4x-22)-25 |